2019
DOI: 10.1186/s13046-019-1467-6
|View full text |Cite
|
Sign up to set email alerts
|

SP600125 enhances C-2-induced cell death by the switch from autophagy to apoptosis in bladder cancer cells

Abstract: BackgroundA natural compound Jaspine B and its derivative possess potential anti-cancer activities; However, little is known about the underlying mechanism. Here, the role of a new autophagy inducer Jaspine B derivative C-2 in suppressing bladder cancer cells was researched in vitro and in vivo.MethodsThe underlying mechanisms and anticancer effect of C-2 in bladder cancer cells were investigated by MTT, western blotting, immunoprecipitation and immunofluorescence assays. The key signaling components were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…Interestingly, scientific evidences described the JNK role in autophagy through Bcl-2 and Bcl-xL phosphorylation to active Beclin-1 [25]. In particular, as previously described, Bcl-2 and Beclin-1 reduction may be a direct consequence of JNK decrease [26]. Therefore, the results discussed so far support the idea that BCP may also regulate apoptosis and autophagy mechanisms not only through a direct modulation of CB2 receptors but also by JNK modulation.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, scientific evidences described the JNK role in autophagy through Bcl-2 and Bcl-xL phosphorylation to active Beclin-1 [25]. In particular, as previously described, Bcl-2 and Beclin-1 reduction may be a direct consequence of JNK decrease [26]. Therefore, the results discussed so far support the idea that BCP may also regulate apoptosis and autophagy mechanisms not only through a direct modulation of CB2 receptors but also by JNK modulation.…”
Section: Discussionsupporting
confidence: 76%
“…Multiple agents in development in preclinical and clinical trials and even many clinical drugs have been found to trigger cytoprotective autophagy, including mTOR inhibitors, kinase inhibitors, natural products, and antiangiogenic agents (Haiyang Yu et al, 2019;Mei-Chuan Chen et al, 2019). Meanwhile, various signaling pathways and molecules have been identified in regulating drug-induced autophagy that impact the outcome of anticancer therapy, such as the PI3K-Akt-mTOR pathway, one of the main regulators of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…A good example of research on a marine-derived compound as possible autophagy modulators is the investigation of jaspine B and its 2-alkylaminomethyl derivatives performed by two different groups [ 80 , 81 ]. Jaspine B is an anhydrophytosphingosine that was first found in the marine sponge Pachastrissa sp.…”
Section: Marine Compounds With a Validated Autophagy-modulatory Efmentioning
confidence: 99%
“…This speculation, however, requires further validation [ 83 ]. Nevertheless, in the following research by Yu et al (Jin group), the authors have applied a number of diverse methods to prove the autophagy-inducing activity of the most promising jaspine B derivative called C-2 in human bladder cancer cells [ 80 ]. Thus, the authors successfully demonstrated the importance of JNK and Nrf2 pathways for the C-2-induced autophagy, which seems to be cytoprotective, in bladder cancer cells.…”
Section: Marine Compounds With a Validated Autophagy-modulatory Efmentioning
confidence: 99%
See 1 more Smart Citation